Recenzja książki Ewy Partygi «Ibsenowskie konstelacje. Ćwiczenia w patrzeniu i czytaniu» (Instytut Sztuki Polskiej Akademii Nauk, Warszawa 2016). - Lech Sokół (Pamiętnik Teatralny, 2018)
Ewa Partyga’s Ibsenowskie konstelacje (Ibsen in Constellations) present the work of Ibsen in various literary, artistic, and philosophical contexts. Perhaps the most brilliant of them belong to the visual constellations, in which the author tackles the relationships between Ibsen and Munch, “Ibsen in the theatre of photography” and “photography in Ibsen’s dramas”, as well as the relationship between Ibsen, Munch, and Vilhelm Hammershøi. The philosophical constellations consist of only to essays. The first uncovers some striking parallels between Ibsen as the author of The Master Builder and Nietzsche as the author of On the Genealogy of Morality. The second text is equally important, because it deals with Ibsen and Kierkegaard with a view to metatheatricality. The Scandinavian and Young Polish constellations focus on the problem of reception of Ibsen’s work in the drama and theatre of Scandinavia and Poland respectively. Partyga examines the problem of Ibsen’s presence in Ingmar Bergman’s theatre; it is the first Polish study on the topic. The Young Polish constellations bring important revisions of Polish myths about Ibsen. A full reception of his oeuvre that encompasses modern translations, artistically rich theatre reception, as well as truly competent theatre and academic criticism in conjunction with a deep audience response has only just begun in Poland. The book Ibsenowskie inspiracje is a part of this new wave and it is an outstanding one.